Organisationalbis justice and cognitive function in middle-aged employees: the Whitehall II study - Elovainio, Marko (J Epidemiol Community Health, 2012)
BACKGROUND: Little is known about the role work-related factors play in the decline cognitive function. We examined the association between perceived organizational justice and cognitive function among middle-aged men and women. METHODS: Perceived organizational justice was measured at Phases 1 (1985–1988) and 2 (1989–1990) of the Whitehall II study when the participants were 35–55 years old. Assessment of cognitive function at the screening clinic at Phases 5 (1997–1999) and 7 (2003–2004) included the following tests in screening clinic: memory, inductive reasoning (Alice Heim 4), vocabulary (Mill Hill), and verbal fluency (phonemic and semantic). Mean exposure to lower organizational justice at Phases 1 and 2 in relation to cognitive function at Phases 5 and 7 were analysed using linear regression analyses. The final sample included 4531 men and women. RESULTS: Lower mean levels of justice at Phases 1 and 2 were associated with worse cognitive function in terms of memory, inductive reasoning, vocabulary and verbal fluency at both Phases 5 and 7. These associations were independent of covariates, such as age, occupational grade, behavioural risks, depression, hypertension and job strain. CONCLUSIONS: This study suggests an association between perceived organizational justice and cognitive function. Further studies are needed to examine whether interventions designed to improve organizational justice would affect employees’ cognition function favourably.